Implementation of video surveillance system using embedded Blackfin processor - Sanket Dessai; Deepa Kannan; Shiva Prasa Yadav (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
The video surveillance is critical system to track the people at the various places and to track and monitor the nuciencess bound to be happened. On the other side several studies have proved and showed the hit and miss nature of human intervention to spot change in a surrounding environment which increasing the designer challenges for the development of video surveillance system with the help of embedded processor. The designer faces a greater challenge to apply the principle of embedded systems and develop the system smart features with low power and cost for the required applications of VSS. System requirement specification (SRS), Hardware design document (HDD), Software design document and test procedure has been arrived and developed to achieve VSS system. Blackfin processor has high end video engines and is more suitable for development of video surveillance system (VSS). The VSS is designed and developed using ADSP BF533 Ez-kit lite board. Peripheral like parallel peripheral interface (PPI) is used to interface between camera and processor. Also, it is used for interfacing processor and TV. The master-slave communication is established between two Blackfin processors through SPORT to transfer the captured frame from camera to display on TV. Power management is also implemented to save the power of the system.